Registration of 'Ho 11‐573' sugarcane. Issue 3 (13th July 2021) - Todd, James; Hale, Anna; Pan, Yong‐Bao; Tew, Thomas L.; Dufrene, Edwis O.; Duet, Michael; Verdun, David; Landry, Cory; Grisham, Michael P.; Kimbeng, Collins; Gravois, Kenneth A.; Bischoff, Keith P.; et al.
Abstract: 'Ho 11‐573' (Reg. no. CV‐201, PI 698597) sugarcane (an interspecific hybrid of Saccharum officinarum L., S. barberi Jeswiet, S. spontaneum L., and S. sinense Roxb. amend. Jeswiet) was selected and evaluated by scientists at the USDA‐ARS, working cooperatively with the Louisiana State University Agricultural Center, the American Sugar Cane League of the U.S.A., Inc., and Rio Farms, Inc. It was released primarily for the Texas sugarcane industry. In field evaluations combined across crops and in ratoons, Ho 11‐573 had yields equivalent to CP 89‐2143 and CP 72‐1210, the most widely grown Texas commercial cultivars. Cane yield (Mg/ha) of Ho 11‐573 from plant‐cane crop evaluations at five locations was significantly higher than CP 89‐2143 or CP 72‐1210. Ho 11‐573 is moderately susceptible to smut and brown rust. It is resistant to leaf scald but is susceptible to ratoon stunt. Sugarcane mosaic and orange rust have not been observed on Ho 11‐573. Core Ideas: 'Ho 11‐573' sugarcane cultivar was released to Texas growers. The cane yield of Ho 11‐573 was comparable to the check cultivars but higher in plant cane. High cane yield makes Ho 11‐573 a useful addition to current sugarcane cultivars in Texas. New cultivars increase diversity and improve the sustainability of the sugarcane industry.